Forest growth and yield modeling - Weiskittel, Aaron R. (Chichester [etc.] : Wiley-Blackwell, 2011)
'Completely updated and expanded new edition of this widely cited book, Modelling Forest Growth and Yield, 2nd Edition synthesizes current scientific literature, provides insights in how models are constructed, gives suggestions for future developments, and outlines keys for successful implementation of models.The book describes current modeling approaches for predicting forest growth and yield and explores the components that comprise the various modeling approaches. It provides the reader with the tools for evaluating and calibrating growth and yield models and outlines the steps necessary for developing a forest growth and yield model'--
1 Introduction -- 2 Indices of competiton -- 3 Forest site evaluation -- 4 Whole-stand and size-class models -- 5 Tree-level models -- 6 Components of tree-list models -- 7 Individual-tree static equations -- 8 Mortality -- 9 Seeding, regeneration, and recruitment -- 10 Linking growth models of different resolutions -- 11 Modeling silvicultural treatments -- 12 Process-based models -- 13 Hybrid models of forest growth and yield -- 14 Model construction -- 15 Model evaluation and calibration -- 16 Implementation and use -- 17 Future directions.
Keywords: Trees -- Growth -- Computer simulation; Forest productivity -- Computer simulation; Trees -- Growth -- Mathematical models; Forest productivity -- Mathematical models; Electronic books